21 Direct oral anticoagulants vs. vitamin K antagonists in the treatment of left ventricular thrombosis: a systematic review and meta-analysis. (8th December 2021) - Condello, Francesco; Maurina, Matteo; Chiarito, Mauro; Sturla, Matteo; Terzi, Riccardo; Fazzari, Fabio; Sanz-Sanchez, Jorge; Cannata, Francesco; Condorelli, Gianluigi; Stefanini, Giulio
Abstract: Aims: Evidence about the use of direct oral anticoagulants (DOACs) in patients with left ventricular thrombosis (LVT) are emerging. The aim of our study was to provide a comprehensive synthesis of the available evidence concerning the clinical effects of DOACs vs. vitamin K antagonists (VKAs) in LVT treatment. Methods: Systematic search of studies evaluating DOACs vs. VKAs use in patients with LVT was performed on 11 May 2021. Data were pooled by meta-analysis using a random-effects model. Odds ratios (OR) with relative 95% confidence intervals (CI) were used as measures of effect estimates. The primary efficacy and safety endpoint were ischaemic stroke and any bleeding, respectively. Secondary endpoints were LVT resolution, systemic embolism, major bleeding, haemorrhagic stroke, and all cause death. Results: Twenty studies were included in the meta-analysis: 1391 patients were treated with DOACs and 1534 with VKAs. A significant reduction in the risk of ischaemic stroke [OR 0.67, 95% CI 0.45–0.98, P  = 0.048, number needed to treat to benefit (NNTB) 22 (95% CI 15–43)] and any bleeding [OR 0.64, 95% CI 0.46–0.89, P  = 0.009, NNTB 26 (95% CI 16–80)] was observed with DOACs compared to VKAs. No statistically significant difference was observed among the two treatment arms for the secondary endpoints. Conclusion: Compared to VKAs, DOACs are associated with a reduced risk of ischaemic stroke and bleeding. In light of these findings, and the practical advantages of DOACs, additional large scale randomized controlled trials are needed to confirm the benefits of DOACs in patients with LVT.